The influence of spiritual leadership and workplace spirituality on knowledge sharing behavior / Nur Kamariah Abdul Wahid - Nur Kamariah , Abdul Wahid (2017)
The dependency of organizations on their employees’ knowledge bank to justify for the overall organizational performance has become a matter of attention. This is because it is easily said than done to motivate employees to share their knowledge in terms of skills, experiences and know-how even with proper package of rewards and incentives. Human capital is in the phase of revolutionizing from merely as working capital to dynamic resources that hold the competitive advantage of the organization. The challenges posited by the dynamic evolution of human capital undeniably challenge the style of leadership too. Studies have shown that an effective leadership style could be a mechanism to induce employees’ engagement so that knowledge sharing would not be an issue to employees. There have been many theories of leadership, approaches to tackle employee engagement, and explorations done to address how to produce a conducive working climate. Leaders should be able to identify the most effective combination qualities of a leadership style. Among many industries, telecommunication industry is known for its dependency in creativity and innovations to meet the dynamic challenges that are linked to employees’ knowledge. As being challenged by obsolete knowledge and skills, the industry needs to always keep their offerings ahead of competitors so that they could control the game field. Leaders of the telecommunication organizations were challenged to find ways to encourage knowledge sharing among employees to keep them fighting confidently on a competitive edge. Thus, the study aimed to explore potentials of involving spiritual values within the framework of leadership and workplace values in order to encourage knowledge sharing behavior. This could be done by knowing how to motivate them to share the knowledge and at the same time enrich the options available for an effective leadership style by exploring and explaining the phenomena of spiritual leadership and workplace spirituality. The research method used in this study enabled the exploration on the interactions between workplace and leaders based on spiritual values that could positively induce motivations to share knowledge to go beyond typical definition by the discovery of deeper level of intrinsic motivations, and cross validated the outcomes to different groups (Morse, 1991), measuring its prevalence.